Limited Rationality and Strategic Interaction: The Impact of the Strategic Environment on Nominal Inertia - Fehr, Ernst; Tyran, Jean-Robert (Econometrica, 2008)
Much evidence suggests that people are heterogeneous with regard to their abilities to make rational, forward-looking decisions. This raises the question as to when the rational types are decisive for aggregate outcomes and when the boundedly rational types shape aggregate results. We examine this question in the context of a long-standing and important economic problem: the adjustment of nominal prices after an anticipated monetary shock. Our experiments suggest that two types of bounded rationality—money illusion and anchoring—are important behavioral forces behind nominal inertia. However, depending on the strategic environment, bounded rationality has vastly different effects on aggregate price adjustment. If agents' actions are strategic substitutes, adjustment to the new equilibrium is extremely quick, whereas under strategic complementarity, adjustment is both very slow and associated with relatively large real effects. This adjustment difference is driven by price expectations, which are very flexible and forward-looking under substitutability but adaptive and sticky under complementarity. Moreover, subjects' expectations are also considerably more rational under substitutability.